IMPLEMENTASI LAYANAN BIMBIGAN KONSELING DALAM MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK DI SMP IT AL-IRSYAD AL-ISLAMIYYAH KARAWANG - Pratama, Ardian Indra; Maryati, Mimin; Munafiah, Nida’ul (Universitas Muhammadiyah Tapanuli Selatan, 2024)
Shared guidance and counseling programs produce program continuity, provide clarity in the direction of program implementation, make it easier to control and evaluate guidance activities, and implement guidance and counseling programs smoothly, effectively and efficiently. The guidance and counseling service program has been discussed in detail in the program planning meeting at SMP IT Al-Irsyad Al-Islamiyyah Karawang. Guidance and counseling service programs must assist with needs assessments to resolve problems currently being experienced by students. The guidance and counseling service program helps assess students' needs to explore their full potential under in-depth guidance from counselors.